Suggested herbal remedies effective on polycystic ovarian syndrome from the viewpoint of Persian medicine - Najmeh Dehparvar; Fatemeh Alijaniha; Seyyed Ali Mozaffarpur; Amir Niasari-Naslaji; Zahra Bahaedin; Ahia Garshasbi; Mohammad Gholami-Fesharak; Mohsen Naseri (Institue of Medicinal Plants, ACECR, 2022)
Background: According to the reverse pharmacological method, traditional medicine has a good source of information for discovering new drug candidates. Polycystic ovarian syndrome (PCOS) is the most common cause of endocrine disorder and infertility among women of reproductive age. This syndrome is commonly treated by oral contraceptive pills; however, it could be associated with side effects. Objective: The purpose of this study was to identify and prioritize medicinal plants proposed by Persian medicine (PM) for the treatment of PCOS. Methods: The first step was to find out the most relevant keywords to the symptoms of PCOS among five authentic PM manuscripts because there was no medical term called PCOS in PM texts. According to those keywords, all materia medicas that was described in the selected books were recorded. Each materia medica received scores based on specific criteria.  The scores were used to prioritize medicaments. Results: Ferula assa-foetida L., Tanacetum parthenium L., Lycium barbarum, Cymbopogon schoenanthus L., Lepidium sativum L. and Marrubium vulgare were six top materia medica identified in this study. Conclusion: Identification of closely related terminology for PCOS in traditional medical texts and prioritization of herbal remedies could be a sound approach to discover new drugs. Accordingly, Ferula assa-foetida L. with the highest score was considered the best candidate for the treatment of PCOS in PM.